Nasionalisme Qurani dan Relevansinya dengan Semangat Kebangsaan Indonesia: Studi QS. [49]: 13, QS. [89]: 8 dan QS. [2]: 143 - Ptiq, lufaefi (IAIN Palangka Raya, 2019)
In the modern era, it emerges a movement wanting to reject the concept of nationalism and replace it with the idea of islamic khilāfah, since nationalism only makes humans become worse. The spirit of life is based solely on competition of hatred and evil (xenophobia). This is caused by reality, since the growing nationalism is not based on the Qur